1995
DOI: 10.1149/1.2048485
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity of Electron Transfer Rates within Nafion Coatings Saturated with Os ( bpy ) 3 2 +  to the Extent of Hydration of the Coating

Abstract: The sensitivity of the electrochemical responses obtained from electroactive counterions incorporated in Nation coatings to the extent of hydration of the coatings 2748 is shown to be enhanced significantly when the electroactive ion is the only counterion present in the coating. Nation coatings fully saturated with Os(bpy)~ + exhibit unusually narrow and sharply peaked anodic currents in first-scan oxidative voltammograms. This voltammetric feature is accompanied by the expulsion of one-third of the Os comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 17 publications
4
27
0
Order By: Relevance
“…Here the MPE increased when the charge passing in the initial part of the anodic scan was omitted. It is also similar to early reports by Anson and coworkers [24,25] that [Os(bpy) 3 ] 3+ ions were ejected from Nafion films saturated with [Os(bpy) 3 ] 2+ during the initial anodic scan. Subsequent EQCM measurements on this system however, revealed that the expulsion of the Os(III) cations resulted in an increase in the mass of the films, attributed to a large inflow of water molecules and of electrolyte counter ions into the films during ejection of the Os(III) ions [26,27].…”
Section: Frequency Changes During Potential Scanssupporting
confidence: 91%
See 1 more Smart Citation
“…Here the MPE increased when the charge passing in the initial part of the anodic scan was omitted. It is also similar to early reports by Anson and coworkers [24,25] that [Os(bpy) 3 ] 3+ ions were ejected from Nafion films saturated with [Os(bpy) 3 ] 2+ during the initial anodic scan. Subsequent EQCM measurements on this system however, revealed that the expulsion of the Os(III) cations resulted in an increase in the mass of the films, attributed to a large inflow of water molecules and of electrolyte counter ions into the films during ejection of the Os(III) ions [26,27].…”
Section: Frequency Changes During Potential Scanssupporting
confidence: 91%
“…They proposed that one [Ru(bpy) 3 ] 3+ ion was ejected out of the films for each three [Ru(bpy) 3 ] 2+ ions oxidized. This is similar to a report that charge neutralization during the electrochemical oxidation [Os(bpy) 3 ] 2+ in Nafion films occurred by ejection of some of the oxidized ions [24,25]. However, the ejection of [Os(bpy) 3 ] 3+ ions from hydrated Nafion films has been reported to result in a mass increase during the initial anodic scan.…”
Section: Introductionsupporting
confidence: 89%
“…These cast films of Nafion retain many of the properties (e.g., water insolubility and ionexchange ability) that characterize Nafion membranes. 22 Shi and Anson 23,24 showed that the ionomer clustering that occurs in membranes also is obtained in spin-coated thin films as evidenced by AC impedance and voltammetric measurements. The spectroscopic data obtained in this study also follow trends seen in IR data obtained with Nafion membranes.…”
Section: Resultsmentioning
confidence: 95%
“…After a very rapid initial uptake, there appears to be a regime of slower incorporation that continues past 75 h of immersion. Shi and Anson 24 reported that Os(bpy) 3 2ϩ loads from a 1 mM solution into hydrated Nafion within 2 h but that in an unhydrated film immersions ranging from 24 -48 h were required to obtain full loading. The initial rate behavior we obtained appears to follow the former profile most closely.…”
Section: Cation Loadingmentioning
confidence: 99%
See 1 more Smart Citation